Quantifying contributions of chlorofluorocarbon banks to emissions and impacts on the ozone layer and climate - Lickley, Megan; Solomon, Susan; Fletcher, Sarah; Velders, Guus J. M.; Daniel, John; Rigby, Matthew; Montzka, Stephen A.; Kuijpers, Lambert J. M.; Stone, Kane (Nature communications, 2020)
Chlorofluorocarbon (CFC) banks from uses such as air conditioners or foams can be emitted after global production stops. Recent reports of unexpected emissions of CFC-11 raise the need to better quantify releases from these banks, and associated impacts on ozone depletion and climate change. Here we develop a Bayesian probabilistic model for CFC-11, 12, and 113 banks and their emissions, incorporating the broadest range of constraints to date. We find that bank sizes of CFC-11 and CFC-12 are larger than recent international scientific assessments suggested, and can account for much of current estimated CFC-11 and 12 emissions (with the exception of increased CFC-11 emissions after 2012). Left unrecovered, these CFC banks could delay Antarctic ozone hole recovery by about six years and contribute 9 billion metric tonnes of equivalent CO 2 emission. Derived CFC-113 emissions are subject to uncertainty, but are much larger than expected, raising questions about its sources. Following international agreements, the use of chlorofluorocarbons in production is supposed to be phased out. Here, the authors present a new estimate of these products already in use and their emissions and show that they are larger than expected and that not recovering these banks leads to a substantial delay in the polar ozone hole recovery.